هەنگاوەكانی حكومەتی هەرێمی كوردستان لە بواری پەروەردە و فێركردن لە شاری سلێمانی (١٩٩٢-٢٠٠٣) - شوانی, پ.ی.د.ئاكۆ عبدالكریم محمود; محمد, خوێندكاری ماسته‌ر: رۆشنا فايق (Sulaimani Journal for Humanities, 2023)
After the establishment of the Kurdistan Regional Government in 1992,educational problems such as not having books and paying teachers' salaries and the reason for not manipulating the education programs and how holding educational conferences to learn more about education situation then started the beginning of political deterioration in Kurdistan till the level of creating two independent administrations in Erbil and Sulaymaniah administration some steps after the decision of 986 to establish the political side and improve the economic situation and to issue a number of decisions to open some educatinol courses by UNESCO and UNICEF to improve the level of teachers' science and learning processes, rehabilitation of the educational institutions and to reform its curriculums. In the same time, it had to care about the training the teaching staff to enhance their scientific capabilities and improving their living standards. So, the ministry of education was the first ministry to be established as soon as the Kurdistan Regional Government was founded. students numbers in Sulamani city.
Keywords: Key words education; government; Sulimaniah; school; student